2020
DOI: 10.18488/journal.1005/2020.10.1/1005.1.141.148
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between socioeconomic status and consumption pattern of fishermen household in Indonesia

Abstract: The purpose of this study is to analyze the relationship between socioeconomic status and consumption patterns of fishermen households in Karangsong Village, Indramayu Regency West Java Indonesia. The importance of this paper comes from the phenomenon of the lifestyle of the fishermen community who is known in general for their very harsh character. This is because their lifestyle is very dependent on nature. Even though in certain seasons fishermen's income will grow very high but in the following seasons, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Animal source foods have been demonstrated to benefit child growth and cognitive development (Neumann et al, 2007; Dror and Allen, 2011;Iannotti et al, 2017;Iannotti, 2018). Here we found that fishing households negatively correlated with CDD, similar to other studies where involvement in fishing activities was not associated with improved household fish consumption (Garaway, 2005;Fiorella et al, 2014;Rusdiana and Mulyawan, 2020). As evidenced from our qualitative research findings, fishing households tend to sell fish in order to purchase the less expensive starch-based foods (Cartmill et al, 2022).…”
Section: Nutrientsupporting
confidence: 88%
“…Animal source foods have been demonstrated to benefit child growth and cognitive development (Neumann et al, 2007; Dror and Allen, 2011;Iannotti et al, 2017;Iannotti, 2018). Here we found that fishing households negatively correlated with CDD, similar to other studies where involvement in fishing activities was not associated with improved household fish consumption (Garaway, 2005;Fiorella et al, 2014;Rusdiana and Mulyawan, 2020). As evidenced from our qualitative research findings, fishing households tend to sell fish in order to purchase the less expensive starch-based foods (Cartmill et al, 2022).…”
Section: Nutrientsupporting
confidence: 88%
“…Indonesians' consumption pattern has varying determinants leading to the volatility viewed from some aspects. Rusdiana et al, (2020) suggests that consumption to fisherman family group is affected by income and number of family members. The relationship between income and consumption in fisherman family group in Indonesia shows that the increased income tends to be used for consumption with MPC of 0.908.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331 136mentioning
confidence: 99%
“…SHAPE_MN represents the complexity of the patch. Lastly, FRAC_MN stands for the degree of irregularity of RSs [ 15 ].…”
Section: Research Scheme Designmentioning
confidence: 99%